An anti-deficit perspective on black male student athletes' educational experiences at a historically black college/university. Issue 5 (2nd September 2016) - Cooper, Joseph N.; Hawkins, Billy
Abstract : The purpose of this study was to identify key institutional characteristics and practices at a historically black college/university (HBCU) that contributed to positive educational experiences for black male student athletes. This mixed methods exploratory study involved the use of a 79-item Student Athlete College Experiences Questionnaire (SACEQ), three focus group interviews, and four individual interviews. Participants in this study included 57 black male football and men's basketball student athletes at an HBCU in the southeastern US. Institutional theory and the anti-deficit achievement framework were incorporated to highlight effective institutional practices at an HBCU. Findings revealed the presence of a nurturing familial campus climate and purposefully designed institutional programs enhanced black male student athletes' educational experiences. Implications for policy and practice are discussed.